Brief Exercise Increases Peripheral Blood NK Cell Counts without Immediate Functional Changes, but Impairs their Responses to ex vivo Stimulation - Millard, Anne-Laure; Valli, Piero V.; Stussi, Georg; Mueller, Nicolas J.; Seebach, Jörg D. (Frontiers in Immunology, 2013)
Regular light-to-moderate physical activity is associated with a reduction of mortality. However, how exercise affects innate immunity remains a matter of debate. It has been know for a long time that physical as well as psychological stress increases the number of circulating peripheral blood NK cells. Whereas some studies found a positive correlation between exercise and NK cell counts and cytotoxic activity, others showed that, for example, heavy training was related to a decrease in per cell NK cytotoxicity. Thus, the impact of exercise on NK cell function and eventually on altered immunocompetence remains to be elucidated. Here, we investigated if a single bout of brief exercise, consisting in running up and down 150 stair-steps, affects the number and function of circulating NK cells. NK cells, obtained from healthy donors, before and immediately after brief exercise, were assessed for numbers, phenotype, IFN production, degranulation, cytotoxicity, and in vitro response to stimulation by IL-2 or TLR2 agonists. Running resulted in a drastic increase in the number of isolated NK cells (6.3-fold). Brief exercise did not significantly interfere with baseline IFNg secretion or NK cell cytotoxicity. Exogenous stimulation enhanced the IFNg-secretion, degranulation and cytotoxicity of NK cells isolated pre-exercise, but had almost no effect on NK cells isolated following exercise. Finally, brief exercise dramatically decreased the frequency of CD56bright NK cells. In conclusion, having no direct impact on NK function, brief exercise might be used as a simple method to increase the number of CD56dim NK cell available for in vitro experiments. Nevertheless, the decrease of the CD56bright NK cells and impaired responses to stimulation suggest a direct impact of brief exercise on NK cell-mediated immunity.